The Effects of Work-Reinforcer Schedules on Skill Acquisition for Children With Autism. (July 2015) - Kocher, Colleen P.; Howard, Monica R.; Fienup, Daniel M.
This study evaluated the effects of continuous and discontinuous work-reinforcer schedule arrangements on skill acquisition for three students with autism. Participants were initially exposed to both schedules in an alternating schedules condition where they were taught different but equivalent skills for each schedule. In the discontinuous schedule condition, participants completed work in small increments to gain access to a reinforcer for short periods of time. In the continuous schedule condition, participants completed larger increments of work to gain longer access to a reinforcer. Results showed that two participants mastered the target responses with both schedules and the third participant only met mastery criterion with the continuous schedule. Preference for schedules varied across participants. Session duration was consistently shorter during the continuous work-reinforcer schedule, suggesting that continuous work-reinforcer schedules are more efficient. Participants engaged with the reinforcer less when provided longer access, suggesting that reinforcer access might be reduced with continuous schedules for further efficiency gains.